2020
DOI: 10.1371/journal.pbio.3000901
|View full text |Cite|
|
Sign up to set email alerts
|

Membrane progesterone receptor induces meiosis in Xenopus oocytes through endocytosis into signaling endosomes and interaction with APPL1 and Akt2

Abstract: The steroid hormone progesterone (P4) mediates many physiological processes through either nuclear receptors that modulate gene expression or membrane P4 receptors (mPRs) that mediate nongenomic signaling. mPR signaling remains poorly understood. Here we show that the topology of mPRβ is similar to adiponectin receptors and opposite to that of G-protein-coupled receptors (GPCRs). Using Xenopus oocyte meiosis as a well-established physiological readout of nongenomic P4 signaling, we demonstrate that mPRβ signal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 76 publications
(131 reference statements)
1
19
0
Order By: Relevance
“…Using transferrin as a marker for clathrin-dependent endocytosis we previously showed that the clathrin-dependent endocytosis inhibitor Pitstop2 (10 -5 M) effectively blocks transferrin uptake (Supp. Figure 3A) 19 (Fig. 3F).…”
Section: Orai1 Internalization Is Not Dependent On Flotillin or Clathmentioning
confidence: 91%
“…Using transferrin as a marker for clathrin-dependent endocytosis we previously showed that the clathrin-dependent endocytosis inhibitor Pitstop2 (10 -5 M) effectively blocks transferrin uptake (Supp. Figure 3A) 19 (Fig. 3F).…”
Section: Orai1 Internalization Is Not Dependent On Flotillin or Clathmentioning
confidence: 91%
“…However, frogs injected with hCG display robust production of androgens rather than P4; suggesting the possibility that androgens are the physiological MIS in Xenopus (Hammes, 2004; Lutz et al, 2001). P4 triggers oocyte maturation either by nuclear progesterone receptor (XPR) bound to the membrane (Bayaa et al, 2000) or by novel G‐protein coupled progestin receptors (mPR; Josefsberg Ben‐Yehoshua et al, 2007; Nader et al, 2020), while androgens function through the classical androgen receptors that are localized throughout oocytes, including within the plasma membrane (Lutz et al, 2003). Both P4 and androgens lower cAMP levels, downregulate PKA activity, and promote new protein synthesis, such as cyclins (B1, B2, B4, and B5), Ringo/Speedy—the non‐canonical activators of CDK1, and Mos—activator of MEK/ERK pathway (Eyers et al, 2005; Ferby et al, 1999; Ferrell, 1999; Haccard & Jessus, 2006b; Hammes, 2004; Meneau et al, 2020; Sadler & Maller, 1981; Wang & Liu, 2004).…”
Section: Oocyte Maturation and Erk Signaling Pathway In Nonmammalian ...mentioning
confidence: 99%
“…Mos, on the other hand, triggers ERK activation which in turn inactivates Myt1, the kinase that blocks Cdk1 activity (Palmer et al, 1998; Peter et al, 2002). Additionally, cAMP/PKA‐independent progesterone‐induced non‐genomic signaling is also documented (Nader et al, 2016), where a signaling endosome of mPRβ interacts with adaptor proteins and Akt2 to promote maturation (Nader et al, 2020). Thus, activation of MPF possibly proceeds through a parallel cAMP/PKA‐dependent and independent pathway and may converge to promote Xenopus oocyte maturation (Figure 3).…”
Section: Oocyte Maturation and Erk Signaling Pathway In Nonmammalian ...mentioning
confidence: 99%
See 1 more Smart Citation
“…Studies of multiple mPR knockouts in zebrafish have confirmed a role in both oocyte maturation and ovulation ( 176 ). In Xenopus oocytes, progesterone binding to mPRβ induced clathrin-dependent endocytosis of mPRβ into the signaling endosome, where mPR interacted transiently with APPL1 and Akt2 to induce meiosis ( 177 ). Additional physiological functions of mPRα include the promotion of sperm motility and the regulation of prolactin secretion.…”
Section: Membrane Progesterone Signalingmentioning
confidence: 99%